Chemical characterization and ultrastructure study of pulp fibers. (September 2020) - Kesari, K.K.; Leppänen, M.; Ceccherini, S.; Seitsonen, J.; Väisänen, S.; Altgen, M.; Johansson, L.-S.; Maloney, T.; Ruokolainen, J.; Vuorinen, T.
Abstract: Understanding the ultrastructure and chemical characterization of pulp fibers is highly important in utilizing wood as a raw material in a wide scope of applications, such as forest biomass-based biorefineries and low-cost renewable materials. The observation of the ultrastructure is not possible without advanced microscopy and spectroscopy techniques. Therefore, this study focuses on exploring the ultrastructure of pulp fibers with helium ion microscopy (HIM) and scanning electron microscopy (SEM). For the analysis of chemical characterization in the pulp fibers, Raman spectroscopy, Fourier transform infrared spectroscopy (FT-IR), and X-ray photoelectron spectroscopy (XPS) were performed. For these studies, the pulp fiber samples were obtained mainly from three different wood species, i.e. spruce, birch and eucalyptus. They were received in the never dried state and dried with a critical point drier (CPD) to minimize pore collapse. The spectroscopy results showed a strong signal from crystalline cellulose and confirmed the absence of lignin after Kraft pulping and bleaching. However, with XPS about 2% of lignin was detected in eucalyptus pulp. The results obtained with the microscopy techniques are compared and indicating the nanofibril size, shape, surface roughness as well as their orientation in pulp fibers. To our knowledge, this is the first time that HIM is applied to study the ultrastructure of pulp fibers and compared against more conventional microscopy and spectroscopy techniques. The main differences between HIM and SEM were found to be related to the focusing and magnification. The individual nano- and microfibrils as well as their bundles were more easily visible with HIM than with SEM. Also, with HIM it was possible to get the total area in focus at once which was not the case with SEM. The increased understanding of the ultrastructure and chemical composition of wood pulp enhance the development of novel wood-based products and processes for their manufacture. Highlights: A comparative study of pulp fibers with helium ion & scanning electron microscopy. Study focuses on fiber porosity, structures, surface characterization & applications. XPS, FT-IR & Raman spectroscopy were used for chemical characterization of fibers. Spectroscopic techniques were used to detect the cellulosic components i.e. lignin.